25-Hydroxycholecalciferol Response to Single Oral Cholecalciferol Loading in the Normal Weight, Overweight, and Obese - Ambreen Ali, Fatima Abid, Asif Islam, Sara Gul, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of the study is to evaluate the response of 25- hydroxycholecalciferol (25OHD) to a single oral administration of cholecalciferol in the normal weight, overweight, and obese individuals. Place and duration of study: The study is conducted in Pak International medical College Hayatabad and the duration of study was from March 2021 to March 2022 Material and Method: We have examined 60 healthy women from the age groups of 24-68 years(mean+ SD, 51.2+ 9.6) with a body mass index in kg/m2 ranging from19.2 to 43.2 (mean + SD 28.2+5.9). Female individuals are divided into 3 groups based on their body mass index, 1st group is having normal female individuals having BMI less than 25 kg/m2 (n=22), 2nd group having BMI of 25.1-29.9 kg/m2(n=23)and 3rd group having BMI greater than 30Kg/m2(n=15). Every participants is taken a single oral dose of cholecalciferol(300,000 IU) and their Venous blood samples are taken to measure the concentration levels of 25OHD, 1,25(OH)2D, parathyroid levels, calcium and phosphorus levels. The results are categorized in the form of mean, standard deviation, p-values, least square means with 95% confidence intervals (CI) in each group of individuals at 8th and 31st days of cholecalciferol administration. Results: The total body fat of normal weight group is significantly lesser than that overweight group of individuals, which is lesser than that of group of obese individuals. At the beseline detection of serum level of 25 OHD all the women have detectable serum levels of 25OHD. In the obese group of individuals there will be a lesser levels of 25 OHD observed than normal group of individuals and the difference is approximately equal in the case of overweight group of individuals. The obese group of individuals also have approximately lesser levels of 1,25(OH)2D than the normal group of individuals but have increasing levels of parathyroid hormones. After administration of cholecalferol the levels of parathyroid hormone is observed significantly lesser at day 8 than baseline in the normal weight of individuals not in other groups, which approximately increasing over time at day 31 in all the groups of individuals. There is a positive correlation found between the concentrations of 25OHD and 1, 25(OH)2D while there is a negative correlation found between the levels of 25 OHD and parathyroid hormone at all time points. Conclusion: Serum levels of 25 OHD become decreases in obese individuals is due to their increase body volume. The levels of decline of 25 OHD in obese is due to their larger body size and slower release of vitamin D from their body fat. Keywords: Adipose tissues, Obesity, Vitamin D, Cholecalciferol, Overweight, Calcium.